Optical modeling of aspherical lenses: a human eye study - Zacharias, C. R.; Amaral, M. M.; Hirtsh, F. D. (Spie - Int Soc Optical Engineering, 2003)
We have been developing a computational code to project optical lenses, with low aberration effects. Our main interest is model the human eye, particularly, project special corrective lenses. As the lens shape is the focus of the optimization, we have coupled a ray tracing method with Monte Carlo techniques. The initial results indicated that the algorithm must be improved in terms of resolution and reliability.
Keywords: eye; ray tracing; optimization; simulation; lenses